PENGARUH PENERAPAN GOVERNMENT ACCOUNTING STANDARD, PEMANFAATAN TEKONOLOGI INFORMASI, DAN INTERNAL CONTROL SYSTEM TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus Pada Organisasi Perangkat Daerah Kecamatan Pakis) - Dina Riski Hartanti; Noor Shodiq Askandar; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The study is aimed at examining government accounting's influence on government accounts, information technology, and internal control system on the quality of the regional financial reports. The study USES an adhesive sampling method, the number of samples in the study are 63 properties of the region working in the village office of ferns. Hypothetical testing on this research using linear regression. According to our t-test results it has been showing significant influence between the government's accounting variabels and the internal control system, the information technology has not significantly affected them. And test f shows a Shared effect on the quality of the local government financial statements. It means that the highest rate of applications for government accounts, information technology, and internal control systems, will be able to produce high-quality accounts.Keywords: Quality of local government financial statements, Government accounting, information technology, And the internal control system.